2015
DOI: 10.1007/s13139-015-0373-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Brainstem Serotonergic Transporter Availability in Adult Migraineurs: an [18F]FP-CIT PET Imaging Pilot Study

Abstract: Purpose Recent studies have proposed central serotonergic dysfunction as a major pathophysiology of migraine. We investigated serotonin transporter (SERT) availability in migrai neurs using F-18-N-(3-fluoropropyl)-2β -carbomethoxy-3β-(4-iodophenyl) nortropane ( Results BP ND at the brainstem was significantly higher in adult migraineurs (n=6, 1.15±0.17) than healthy subjects (0.95 ± 0.14) (p = 0.04). Healthy subjects demonstrated negative correlation between brainstem BP ND and age (r= −0.64, p=0.02), whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, although the sample size may seem small in clinical research, in molecular research, it is considered a moderate sample size. For example, PET imaging studies in human use comparable sample sizes [4750]. Importantly, despite the small sample size, we were able to show a statistically significant effect for lead after a Bonferroni correction for multiple comparisons.…”
Section: Discussionmentioning
confidence: 80%
“…Furthermore, although the sample size may seem small in clinical research, in molecular research, it is considered a moderate sample size. For example, PET imaging studies in human use comparable sample sizes [4750]. Importantly, despite the small sample size, we were able to show a statistically significant effect for lead after a Bonferroni correction for multiple comparisons.…”
Section: Discussionmentioning
confidence: 80%
“…[123I]β-CIT used most prominently in SPECT imaging of DAT has high affinity for the serotonin transporter (SERT) 77 and is based off a chemistry sensitive to selective serotonin reuptake inhibitor medications 78 , 79 . In fact, FP-CIT tracers have been used to image SERT 80 , 81 , which has reasonably high distribution in the striatum 82 , 83 . The previously observed positive relationship between [123I]FP-CIT BP ND and BIS-11 28 could thus result from differences in FP-CIT specificity for DAT relative to SERT versus the greater DAT specificity of the FE-PE2I tracer we used here 84 .…”
Section: Discussionmentioning
confidence: 99%
“…By using neuroimaging methods (SPECT-images coregistered with MRI-scans) (Schuh-Hofer et al, 2007) it was shown that there is an increased availability of 5-HTT in brainstem in migraine patients during the interictal period. The recent PET-study also confirms that the 5-HTT availability is crucial in the pathomechanisms of migraine (Park et al, 2016). The limitation of the complete comparison of our results with the clinical studies is that the human observations are examining migraine during the interictal period opposite the NTG model of migraine, which is the ictal model of migraine.…”
Section: Discussionmentioning
confidence: 62%